The Bem Sex-Role Inventory: Proposal of a short version in Spanish - Gómez Berrocal, Carmen; Cervilla, Oscar; Álvarez-Muelas, Ana; Sierra, Juan Carlos (Anales de Psicología / Annals of Psychology, 2022)
The study objective was to examine the factorial structure, reliability and to provide some evidence for validity of the Spanish version of the Bem Sexual Roles Inventory (BSRI), which assesses self-description in terms of gender traits. A sample of 2,672 Spanish participants, heterosexual adults (1,289 men, 1,383 women) distributed into four age groups (18-25, 26-35, 36-55, 56 years or more), completed a Spanish 40-item version of BSRI. An 8-item scale is proposed with a two-dimensional structure: Masculinity (M) and Femininity (F). Both factors present adequate reliabi-lity. Regarding evidence for validity, men (vs. women) scored higher in M, and women (vs. men) in F. The M scores were higher for the participants aged less than 56 years. No differences were found in the F scores among age groups. We discuss the usefulness of this measure to assess interindividual differences, across sex and age, in the self-attribution of traditional gender traits.